Analyses of plant products in greater detail - Paloheimo, L.; Vainio, K. A.; Kero, M.-L.; Herkola, Eine (Agricultural and Food Science, 1961)
The customary Weende system for food analysis is biologically defective and even misleading. The authors have used an analysis scheme in which the conventional crude fibre determination is replaced by the determination of the total of the vegetable cell wall substances. This fraction is called membrane substances. The crude fibre is an arbitrary fragment of this total. E.g. in spruce wood the crude fibre forms about 80 % of the total of the membrane substances, and in wheat bran about 50 %. In addition the fraction »membrane substances» is divided into 4 subtractions: cellulose, pentosans, lignin, and other membrane substances. Further, a fraction called valuable carbohydrates is determined by subtracting from 100 the percentages of water, ash, crude protein, crude fat, and membane substances. This scheme has been applied to the investigation of 44 different plant products. A critical examination of the methods used has been included.